I, witness - McClintock, Norah (Custer, WA : Orca Book Publishers, 2012)
Boone and Robbie witness a violent murder and decide to keep it to themselves, but then Robbie is murdered and another friend soon after. Boone decides he needs to figure out who is killing his friends, and why. Soon the cops and the bad guys are after him, and Boone has to decide what the truth is worth.
Ages 12 and up.